Traduire pour transmettre: le cas des textes amérindiens. - Cyr, Danielle; Sévigny, Alexandre (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article explores two sorts of problems that postcolonial amerindian translation poses: grammatical facts and socio-cultural context. In a first section, we discuss specific grammatical facts occurring in some First Nations languages that pose difficulties to the translator. In a second section, we discuss the process of translation of amerindian texts, concentrating on who is doing the translating and the importance of translation to the survival of endangered amerindian languages. All discussion is framed by the fact that amerindian languages are currently situated in amerindian cultures which are the product of colonial influences that shaped the socio-historical context within which amerindian languages evolved. These problems are discussed with specific reference to Mìgmaq, Innu and Montagnais, all endangered amerindian languages spoken in Canada and the United States. The target languages for the translations are either French or English.